2022
DOI: 10.1186/s12944-022-01697-9
|View full text |Cite
|
Sign up to set email alerts
|

Fat-to-muscle ratio as a predictor for dyslipidaemia in transitional-age youth

Abstract: Background Although dyslipidaemia may have a crucial impact on cardiovascular health in adults, there is a lack of specific data in transitional-age youth. Therefore, this study attempted to evaluate the association of dyslipidaemia with fat-to-muscle ratio (FMR), and establish FMR thresholds for diagnosing dyslipidaemia in transitional-age youth. Methods One thousand six hundred sixty individuals aged 16 to 24 years from the baseline of a subcohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…High LCI by ADP predicted dyslipidemia, and participants with high versus low LCI by ADP or US had a worse cardiometabolic profile. Previous research has also demonstrated a relationship between dyslipidemia, 39 metabolic syndrome, 40 and hyperinsulinemia 41 and the ratio of FM to skeletal muscle (or related compartments) in the pediatric population 42 . Our findings therefore support the concept that having a higher LCI, or a greater adipose tissue than muscle mass also known as the sarcopenic obesity phenotype in older adults, poses a physiological overload that the available muscle mass cannot overcome, increasing the risk of cardiometabolic dysfunction.…”
Section: Discussionsupporting
confidence: 85%
“…High LCI by ADP predicted dyslipidemia, and participants with high versus low LCI by ADP or US had a worse cardiometabolic profile. Previous research has also demonstrated a relationship between dyslipidemia, 39 metabolic syndrome, 40 and hyperinsulinemia 41 and the ratio of FM to skeletal muscle (or related compartments) in the pediatric population 42 . Our findings therefore support the concept that having a higher LCI, or a greater adipose tissue than muscle mass also known as the sarcopenic obesity phenotype in older adults, poses a physiological overload that the available muscle mass cannot overcome, increasing the risk of cardiometabolic dysfunction.…”
Section: Discussionsupporting
confidence: 85%